THE MECHANISM OF HARDENING OF ALLOYED STEELS IN IMPULSE MAGNETIC FIELD - A. V. Alifanov; Zh. A. Popova; N. M. Tsionenko (Литьë и металлургия)
In this paper, a model describing the mechanism of hardening steels in a pulsed magnetic field is provided. The model is based on the consideration of induction currents in the grain bulk ferrite, on the surface of the workpiece near the inductor. The influence of doping efficiency of the process of hardening is established.